Bacterial and chemical pollution level of the river Turag, Gazipur, Bangladesh (Dhaka University Journal of Biological Sciences, 2017)
The river Turag is the upper tributary of the river Buriganga in Bangladesh. Aerobic heterotrophic bacterial count of the river in nutrient agar (NA) and peptone yeast extract glucose (PYG) agar media ranged from 2.91 × 105 to 27.5 × 105 cfu/ml and from 1.09 × 105 to 19.3 × 105 cfu/ml, respectively. Enteric and related bacterial count on MacConkey agar was between 0.88 × 103 and 20.8 × 103 cfu/ml. Out of 91 isolated bacterial isolates, 30 were selected based on their distinctive colony morphology for detailed study. Among these, 16 were Grampositive (53%) and 14 were Gram-negative (47%). Bacillus was dominant among the Gram-positive isolates (69%). The remaining were Brochothrix thermosphacta (6%), Caryophanon sp. (19%) and Renibacterium salmoninarum (6%). Fourteen Gram-negative, enteric and related isolates were identified as Plesiomonas shigelloides (43%), Alcaligenes denitrificans (22%), E. coli (14%), Proteus (14%) and Citrobacter freundii (7%). Biological oxygen demand (BOD) and chemical oxygen demand (COD) values were about 9 and 5-fold higher than standard values whereas dissolved oxygen (DO) of the river was found to be six times less than the standard value. The maximum average TDS, conductivity and turbidity was recorded during the summer season as 441.75 ± 15.52 mg/l, 858.25 ± 19.57 μS/cm and 79.53 ± 6.49 NTU, respectively. Chemical contents viz. sulphate, chloride and fluoride were found to be satisfactory from pollution point of view. Both BOD and COD values along with the abundance of different heterotrophic and enteric bacteria clearly indicated that the river Turag was polluted with organic, chemical and bacterial pollutants.Dhaka Univ. J. Biol. Sci. 26(1): 1-11, 2017 (January)